2012
DOI: 10.1016/j.dental.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of surface treated cast titanium with Nd:YAG laser

Abstract: Objective: To investigate the effect of laser surface treatment of cast titanium alloy on microstructure and mechanical properties.Methods: Dumbbell-and plate-shaped cast titanium specimens were prepared for mechanical testing and microstructure analysis. After the cast surfaces of each specimen were laser-treated using a dental Nd:YAG laser machine at 240 V and 300 V with and without argon gas shielding, tensile testing and microstructure analysis were conducted.Hardness depth profiles were also made from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
2
26
0
1
Order By: Relevance
“…Consequently, improvements in machinery performance and safety in aerospace, automotive, can be realized by the method [21]. According to Poulon-Quintin et al [22], laser beams, because of specific thermal characteristics induced by laser irradiation, can generate specific microstructures including metastable phases and nano-crystalline grains. Laser processing offers unique and significant quality and cost advantages over traditional techniques.…”
Section: Direct Laser Metal Depositionmentioning
confidence: 99%
“…Consequently, improvements in machinery performance and safety in aerospace, automotive, can be realized by the method [21]. According to Poulon-Quintin et al [22], laser beams, because of specific thermal characteristics induced by laser irradiation, can generate specific microstructures including metastable phases and nano-crystalline grains. Laser processing offers unique and significant quality and cost advantages over traditional techniques.…”
Section: Direct Laser Metal Depositionmentioning
confidence: 99%
“…Some studies have reported that welded structures present worse properties than cast specimens, such as lower mechanical resistance, higher corrosion and increased pore incorporation (11,22). Using scanning electron microscopy, it was observed that the laser-welding region is not completely melted and the 0.7 mm penetration depth reduced specimen's resistance, indicating that this method is not suitable for welding surfaces exceeding 1 mm in diameter (22).…”
Section: Discussionmentioning
confidence: 99%
“…The laser process is the most common method used to weld titanium. It is characterized by a monochrome electromagnetic light whose energy beam can be concentrated in a focal point resulting in the union process (11). Some advantages of this method are the absence of direct contact with the welded area, more defined welding area with less heating and no influence of magnetic field on the laser beam (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this, vaporization is avoided due to rapid heating and solidification of the molten clad, which helps to inhibit long-range diffusion, avoid crystallization, achieve strong metallurgical bond with the substrate, and increase hardness [6,34]. Laser beam-specific thermal characteristics induced by laser irradiation help generate specific microstructures, including metastable phases and nano-crystalline grains, which is an advantage over conventional techniques [35]. The most important factor to consider during cladding process is the melting of the alloying material to the substrate.…”
Section: Laser Surface Claddingmentioning
confidence: 99%